Health literacy, including related vaccination, of the working Russian population: data from a survey on the Atria platform - A. A. Antsiferova; M. V. Lopatina; A. V. Kontsevaya; P. V. Ipatov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Health literacy (HL), including related vaccination, is an important health determinant. For the working population, it helps to maintain and improve their ability to work. Despite the clear benefits of vaccination, vaccine confidence has recently declined worldwide, which may lead to decreased vaccination coverage and a renewal of infectious diseases. Based on this, increasing the level of public health, including vaccination issues, is one of the preventive medicine tasks. Staff groups seem to be an effective place for implementing measures to improve the health and vaccination prevention of the working population.Aim. To assess the level of public health, including vaccination issues, among the working Russian population using digital technologies.Material and methods. The study was conducted online and included employees filling out a questionnaire on their own. The results were posted on the Atria digital platform, which is a tool for assessing and implementing corporate programs to improve employee health. HL was assessed using the updated 2019 Health Literacy Survey Questionnaire (HLS19-Q) adapted into Russian and validated. The study lasted 18 months (from December 2022 to May 2024).Results. A total of 58357 employees took part in the study on the Atria digital platform to assess the public health level, of which 47044 (80,6%) were women. In general, workers had a predominantly excellent HL (n=39637, 67,9%), while in women it was 69,4% (n=32644). The insufficient HL varied slightly among workers of different age groups. The fewest workers with an excellent HL were recorded in the age group of 40-49 years (65,4%, n=11857), and the most among workers >60 years old (74,2%, n=3573). The study found that 43,3% of men and 56,2% of women are vaccinated against influenza annually. Among those workers who are vaccinated against influenza annually, the highest HL rate was recorded among workers >60 years of age (63,4%, n=4188), and the lowest among workers <30 years of age (48,2%, n=4992). Workers with an excellent HL are predominantly vaccinated against influenza annually (77,8%, n=21306).Conclusion. For the first time in the Russian Federation, a study was conducted to assess the HL level, including vaccination issues, among workers using digital technologies. The results obtained indicate that further measures are needed to increase the HL level of workers, including in terms of vaccination. Based on research data, methodological documents and corporate programs aimed at improving the current situation should be developed and implemented.